Efficacy of acarbose in different geographical regions of the world: analysis of a real‐life database1. Issue 2 (12th October 2014) - Weng, Jianping; Soegondo, Sidartawan; Schnell, Oliver; Sheu, Wayne H.‐H.; Grzeszczak, Wladyslaw; Watada, Hirotaka; Yamamoto, Noriyuki; Kalra, Sanjay
Abstract Background Alpha‐glucosidase inhibitors are recommended in some international guidelines as first‐line, second‐line and third‐line treatment options but are not used worldwide due to perceived greater effectiveness in Asians than Caucasians. Methods Data from ten post‐marketing non‐interventional studies using acarbose, the most widely used alpha‐glucosidase inhibitor, from 21 countries, provinces and country groups were pooled. Effects on glycated hemoglobin (HbA1c) were analysed for four major ethnicity/region groups (European Caucasians and Asians from East, Southeast and South Asia) to identify differences in the response to acarbose. Results The safety and efficacy populations included 67 682 and 62 905 patients, respectively. Mean HbA1c in the total population decreased by 1.12 ± 1.31% at the 3‐month visit from 8.4% at baseline (p < 0.0001). Reductions in HbA1c, fasting plasma glucose and post‐prandial plasma glucose were greater in patients with higher baseline values. Acarbose was well tolerated, with few episodes of hypoglycemia (0.03%) and gastrointestinal adverse events (2.76%). Data from 30 730 Caucasians from Europe and Asians from three major regions of Asia with non‐missing gender/age information and baseline/3‐month HbA1c data were analysed by multivariable analyses of covariance. After adjustment for relevant baseline confounding factors, Southeast and East Asians had slightly better responses to acarbose than South Asians and European Caucasians; however, the differences were small. Conclusions Acarbose was effective in both European Caucasians and Asians; however, after adjustment for baseline confounding factors, significant small differences in response favoured Southeast and East Asians. © 2014 The Authors. Diabetes/Metabolism Research and Reviews published by John Wiley & Sons, Ltd.